MARX’S QUASI-CRIMINOLOGICAL SATIRE AND CURRENT THEORETICAL CONCERNS ON CYBERCRIME - Kilakos, Dimitris (International Journal of Law in Changing World, 2024)
This paper addresses theoretical concerns on crime and technological innovation enabling cybercriminal activities by reflecting on Marx’s short satirical essay “Apologist Conception of the Productivity of all Professions” to discuss criminological challenges posed by cybertechnologies. To a certain extent, it could be argued that the epistemological challenges posed to criminological theories by the development of cybercrime stem from the mediational role of digital technologies and the social dynamics that frame their potentially criminal uses. Social studies of technology may arguably inform ways to meet such challenges. To address this issue, the paper discusses the case for the role of hacking in developing the so-called cyberculture and the technological devices enabling it. In this regard, it is argued that Marx’s short essay may become insightful for discussing the relationship between crime and technological innovation, informing theoretical concerns that bear significant practical, criminological, legal and jurisprudential consequences. __________ Este artículo aborda preocupaciones teóricas sobre el crimen y la innovación tecnológica que facilita las actividades cibercriminales, reflexionando sobre el breve ensayo satírico de Marx, "La concepción apologética de la productividad de todas las profesiones", para discutir los desafíos criminológicos planteados por las cibertecnologías. En cierta medida, podría argumentarse que los desafíos epistemológicos que el desarrollo del cibercrimen plantea a las teorías criminológicas se derivan del papel mediador de las tecnologías digitales y las dinámicas sociales que enmarcan sus posibles usos delictivos. Los estudios sociales de la tecnología pueden, posiblemente, proporcionar enfoques para enfrentar estos desafíos. Para abordar este tema, el artículo discute el papel del hacking en el desarrollo de la llamada cibercultura y los dispositivos tecnológicos que la habilitan. En este sentido, se argumenta que el breve ensayo de Marx puede ser esclarecedor para discutir la relación entre el crimen y la innovación tecnológica, informando preocupaciones teóricas que tienen importantes consecuencias prácticas, criminológicas, legales y jurisprudenciales. __________ 本文通过反思马克思的短篇讽刺文章《所有职业生产力的辩护士观念》，探讨了犯罪与技术创新促进网络犯罪活动的理论问题，以讨论网络技术带来的犯罪学挑战。在一定程度上，可以认为网络犯罪的发展给犯罪学理论带来的认识论挑战源于数字技术的中介作用及其潜在犯罪用途所涉及的社会动态。技术的社会研究可能为应对这些挑战提供见解。为了解决这一问题，本文探讨了黑客行为在所谓“网络文化”发展中的作用及其所依赖的技术设备。从这一角度来看，马克思的短篇文章可能为探讨犯罪与技术创新之间的关系提供启发，从而为具有重大实践、犯罪学、法律和法理学意义的理论问题提供参考。